2009
DOI: 10.1111/j.1365-2516.2009.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of variations in the reported haemophilia A prevalence around the world

Abstract: The objectives of this paper were to study the reported haemophilia A prevalence (per 100 000 males) on a country-by-country basis and address the following: Does the reported prevalence of haemophilia A vary by national economies? We collected prevalence data for 106 countries from the World Federation of Hemophilia (WFH) annual global surveys and the literature. We found that the reported haemophilia A prevalence varied considerably among countries, even among the wealthiest of countries. The prevalence (per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(202 citation statements)
references
References 60 publications
(89 reference statements)
11
181
1
9
Order By: Relevance
“…These results were in concordant with the results of multiple previous studies [4], [7]- [9] where the majority of hemophilic cases in their studies were hemophilia A. Also, in the present study, the majority of diagnosed hemophilia cases 51 (68%) their ages were less than 25 years old and only 24 (32%) were more than 25 years old, these results were in agreement with the results of Stonebraker et al [3] and with KAR et al [8] , where the majority of diagnosed hemophilia cases were younger than 25 years old. Gender distribution revealed that 71(94.7%) were males and 4(5.3%) were females.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results were in concordant with the results of multiple previous studies [4], [7]- [9] where the majority of hemophilic cases in their studies were hemophilia A. Also, in the present study, the majority of diagnosed hemophilia cases 51 (68%) their ages were less than 25 years old and only 24 (32%) were more than 25 years old, these results were in agreement with the results of Stonebraker et al [3] and with KAR et al [8] , where the majority of diagnosed hemophilia cases were younger than 25 years old. Gender distribution revealed that 71(94.7%) were males and 4(5.3%) were females.…”
Section: Discussionsupporting
confidence: 83%
“…So individuals presenting with history of easy bruising, spontaneous joint bleeding, soft tissue hematomas, hematuria or excessive bleeding after trauma or in the post operative setting should be suspected and evaluated for haemophilia. [3] In Egypt which has a population of approximately (90 millions) and frequent consanguineous marriage , autosomal recessive disorders are more prevalent than other areas of the world. According to World Federation of Haemophilia(WFH) survey, 80% of haemophilia patients in the world don't receive any treatment and usually do not survive till adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…
Haemophilia A (factor VIII deficiency) is the most common type of haemophilia [1], affecting approximately 1 in 5000 males, although its prevalence varies globally [2] This letter presents a preplanned interim analysis of data collected up to September 1, 2012 for the guardian TM 2 extension trial. The primary objective is to assess the safety of turoctocog alfa for prevention and treatment of bleeds.
…”
mentioning
confidence: 99%
“…Поширеність гемофілії у районі була визначена як 1:6194, на Заході України вона становить 1:8385, у Білорусі -1:7752, у Росії -1:4386 [13], у Європі вона складає від 1:2591 у Ісландії до 1:18182 у Боснії та Герцеговині [42], а середньосві-товий показник оцінюється як 1:10000 [41].…”
Section: Sadovnychenko@gmailcomunclassified